Ultrastructure of synapses in the supraoptic nucleus of the cat after induced hypothermia - Malínská, J; Malínsky, J (Acta Universitatis Palackianae Olomucensis Facultatis Medicae, 2000)
Ultrastructure of axosomatic (AS) and axodendritic (AD) synapses in the supraoptic nucleus (NSO) was investigated in a group of normothermic cats and compared with another group of cats after short-term induced hypothermia. Quantitative analysis demonstrated a significant decrease of number of AS synapses, smaller size of AD synaptic knobs, shorter length of the synaptic contact and an increase of the active zone. Evaluation of the shape of the synaptic cleft demonstrated an increase of both positive (P) and negative (N) types in hypothermic animals. The observed morphological changes can be ascribed to the decreased synaptic activity in a greater part of the synaptic population and to the increased activity in a smaller portion of synapses.
Keywords: Dendrites; Animals; nucleus supraopticus; synapse; dendrity; hypotermie; Cats; Supraoptic Nucleus; zvířata; Synapses; Hypothermia; axony; Reference Values; kočky; referenční hodnoty; Axons